TWISTS AND TURNS OF PROBLEMS AND CHALLENGES IN THE WORLD OF EDUCATION REGARDING THE IMPACT OF INSTANT CULTURE ON TECHNOLOGICAL DEVELOPMENT IN THE POST MODERN ERA - Budiatmaja, Rudy; Dully, Stefanus (Universitas Sanata Dharma, 2024)
Problem of education in the modern era is not only limited to systems, methods and strategies, but more about how to prepare future generations. The phenomenon in the modern era shows that the younger generation is growing up with an individualistic and pragmatic attitude. So that many graduates of educational institutions are trapped in understanding their teachings more deeply, so that the priority of the world of education, which is actually very broad, becomes stagnant and narrow because it is only for themselves. Researchers use qualitative data as research material as a research method by first analyzing various literary sources which dominate the occurrence of several current instant culture phenomena due to technological advances. Then the second method is expected to get the best solution for the world of education, especially the millennial generation in accepting instant culture as a result. technological change and progress. The results of this research are that we all cannot withstand the influx of instant culture with increasingly rapid technological developments so that the world of education, especially the millennial generation, must be positive and critical in facing changes in instant cultural values so that we do not fall into it and the final conclusion is that we strive to use this instant culture in accordance with God's teachings and commands and in accordance with our Pancasila values.